Legal Dilemma between Law on Protection Child and Marriage Law in Addressing Early Marriage - Winsherly Tan; Agustianto Agustianto; Febri Jaya (Justisi, 2024)
This study aims to analyze marriage regulations with child protection, namely Law Number 16 of 2019 on Marriage and Law Number 35 of 2014 on Child Protection. These two regulations will be analyzed to protect children who marry underage. The study method used is normative juridical. As a novelty, the study tries to compare marriage arrangements with child protection arrangements. The purpose and perspective of underage marriage between the two regulations are different. The research results show that marriage law has a different spirit than child protection law. This is shown in the marriage law, which states that children are still allowed to marry for urgent reasons by applying for a dispensation to the court. However, child protection law explicitly does not allow this. Therefore, there is a need for more detailed regulation regarding the category of "urgent reasons" regulated in the marriage law.